2014
DOI: 10.1111/jvim.12343
|View full text |Cite
|
Sign up to set email alerts
|

Canine T‐Zone Lymphoma: Unique Immunophenotypic Features, Outcome, and Population Characteristics

Abstract: BackgroundCanine T‐cell lymphoma (TCL) is clinically and histologically heterogeneous with some forms, such as T‐zone lymphoma (TZL), having an indolent course. Immunophenotyping is an important tool in the classification of TCL in people, and can be equally useful in dogs.Hypothesis/ObjectivesWe hypothesized that loss of expression of the CD45 antigen is a specific diagnostic feature of TZL.AnimalsTwenty dogs with concurrent histology and immunophenotyping by flow cytometry were studied in depth. An additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
215
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(243 citation statements)
references
References 31 publications
24
215
2
2
Order By: Relevance
“…Boxers often develop lymphoblastic T-cell lymphomas as well as peripheral T-cell lymphoma (PTCL) (Lurie et al 2008), both aggressive forms of T-cell lymphoma (Frantz et al 2013), whereas golden retrievers are more prone to developing T-zone lymphomas that are relatively mild and have not been described in humans (Fosmire et al 2007;Seelig et al 2014). The typical mutation pattern in those two breeds is remarkably distinct.…”
Section: Discussionmentioning
confidence: 95%
“…Boxers often develop lymphoblastic T-cell lymphomas as well as peripheral T-cell lymphoma (PTCL) (Lurie et al 2008), both aggressive forms of T-cell lymphoma (Frantz et al 2013), whereas golden retrievers are more prone to developing T-zone lymphomas that are relatively mild and have not been described in humans (Fosmire et al 2007;Seelig et al 2014). The typical mutation pattern in those two breeds is remarkably distinct.…”
Section: Discussionmentioning
confidence: 95%
“…B-cell count was determined by multiplying the white blood cell (WBC) by the percentage of cells in the blood that expressed CD21 but did not express CD5. T-cell CLL cases were diagnosed based on the presence of a lymphocytosis (greater than 5000 lymphocytes/μl) comprising an expansion of T cells (CD3+) with no significant increase in other lymphocyte subsets, small cell size determined by flow cytometry, and a cytologic description of Bsmall^or Bmature.^A large subset of cases (35/46) met the diagnostic requirements of T zone lymphoma/leukemia (TZL), an indolent lymphoma that in most cases features circulating neoplastic lymphocytes resulting in a lymphocytosis (FloodKnapik et al 2013;Seelig et al 2014). Inclusion criteria for TZL cases were lymphocytosis (greater than 5000 lymphocytes/μl) with greater than 25 % of the lymphocytes being T cells that do not express the pan-leukocyte antigen CD45.…”
Section: Case Recruitment and Immunophenotypingmentioning
confidence: 98%
“…Inclusion criteria for TZL cases were lymphocytosis (greater than 5000 lymphocytes/μl) with greater than 25 % of the lymphocytes being T cells that do not express the pan-leukocyte antigen CD45. These criteria have been shown to be diagnostic for TZL (Seelig et al 2014). CD34+ cases were designated as AML when associated with an expansion of CD14-positive leukocytes (Villiers et al 2006), while cases with CD5 expression were designated as ALL.…”
Section: Case Recruitment and Immunophenotypingmentioning
confidence: 99%
“…It appears to be a biologically and genetically distinct form with a different molecular profile, and dogs with TZL have a markedly better prognosis (Flood-Knapik and others 2013, Frantz and others 2013, Valli and others 2013). Breeds at higher than expected risk for TZL were golden retrievers and shih tzus (Seelig and others 2014). …”
Section: Types Of Tcl In Dogsmentioning
confidence: 99%
“…One study showed that expression of CD21 (complement receptor-2) was high in TZL, therefore, co-expression of CD21 and CD3 may act as a marker for this disease when histology and flow cytometry are not available (Frantz and others 2013). A further flow cytometry study identified TZL having lymphocytes that were CD4+, but had a specific aberrant lack of CD45 (ie, the cells are CD45 negative) (Seelig and others 2014). Lymphocytosis occurs in more than half of TZL patients (Flood-Knapik and others 2013, Martini and others 2016).…”
Section: Types Of Tcl In Dogsmentioning
confidence: 99%